What we mean when we talk about freedom – The KOMFOR study: an analysis of students' choices of courses in interdisciplinary parts of the curriculum. - Seifert, Andreas; Strunz, Cathleen; Gunkel, Marjaana; Schütz, Julia (INTED2014 Conference Proceedings: 8th International Technology, Education and Development Conference March 10th-12th, 2014 – Valencia, Spain)

Der Test zur Messung bildungswissenschaftlichen Wissens (BwW) als Beispiel der handlungsorientierten Operationalisierung kognitiver Fähigkeiten. - Seifert, Andreas (11. Sommerschule der Fakultät für Erziehungswissenschaft der Universität Hamburg.)

Wahlfreiheit am Lernort Hochschule – Die KOMFOR-Studie: Zum Wahlverhalten in fachübergreifenden Studienangeboten. - Seifert, Andreas; Schütz, Julia (DGHD-Tagung „Leitkonzepte der Hochschuldidaktik: Theorie – Praxis – Empirie")

Freiheit, die ich meine: Zum Wahlverhalten in fachübergreifenden Studienangeboten – Nomothetische und ideographische Zugänge. - Schütz, Julia; Seifert, Andreas (AEPF-Tagung „Der Forschung / Der Lehre / Der Bildung”)

Konzeptionen der Kompetenz und Möglichkeiten der Operationalisierung. - Seifert, Andreas (11. Sommerschule der Fakultät für Erziehungswissenschaft der Universität Hamburg.)

Freiheit, die ich meine: Zum Wahlverhalten in fachübergreifenden Studienangeboten – Beispiel Leuphana College. - Beck, Karin; Seifert, Andreas (Tag der Lehre an der Universität Paderborn)

Kompetenz: ein schillernder Begriff. - Seifert, Andreas (Fortbildungstag für Berufsberater_innen: „Studienziel: Employability”)

Co-development of manner and path concepts in language, action, and eye-gaze behavior - Lohan, Katrin S.; Griffiths, Sascha; Sciutti, Alessandra; Partmann, Tim C.; Rohlfing, Katharina (Topics in Cognitive Science)
In order for artificial intelligent systems to interact naturally with human users, they need to be able to learn from human instructions when actions should be imitated. Human tutoring will typically consist of action demonstrations accompanied by speech. In the following, the characteristics of human tutoring during action demonstration will be examined. A special focus will be put on the distinction between two kinds of motion events: path-oriented actions and manner-oriented actions. Such a distinction is inspired by the literature pertaining to cognitive linguistics, which indicates that the human conceptual system can distinguish these two distinct types of motion. These two kinds of actions are described in language by more path-oriented or more manner-oriented utterances. In path-oriented utterances, the source, trajectory, or goal is emphasized, whereas in manner-oriented utterances the medium, velocity, or means of motion are highlighted. We examined a video corpus of adult-child interactions comprised of three age groups of children-pre-lexical, early lexical, and lexical-and two different tasks, one emphasizing manner more strongly and one emphasizing path more strongly. We analyzed the language and motion of the caregiver and the gazing behavior of the child to highlight the differences between the tutoring and the acquisition of the manner and path concepts. The results suggest that age is an important factor in the development of these action categories. The analysis of this corpus has also been exploited to develop an intelligent robotic behavior -the tutoring spotter system-able to emulate children's behaviors in a tutoring situation, with the aim of evoking in human subjects a natural and effective behavior in teaching to a robot. The findings related to the development of manner and path concepts have been used to implement new effective feedback strategies in the tutoring spotter system, which should provide improvements in human-robot interaction.
Keywords: Imitation; Tutoring; Adult-child interaction; Human-robot interaction; Semantics; Teachable robots

Robots show us how to teach them: Feedback from robots shapes tutoring behavior during action learning - Vollmer, Anna-Lisa; Mühlig, Manuel; Steil, Jochen J.; Pitsch, Karola; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (PLoS ONE)
Robot learning by imitation requires the detection of a tutor's action demonstration and its relevant parts. Current approaches implicitly assume a unidirectional transfer of knowledge from tutor to learner. The presented work challenges this predominant assumption based on an extensive user study with an autonomously interacting robot. We show that by providing feedback, a robot learner influences the human tutor's movement demonstrations in the process of action learning. We argue that the robot's feedback strongly shapes how tutors signal what is relevant to an action and thus advocate a paradigm shift in robot action learning research toward truly interactive systems learning in and benefiting from interaction.

Intermodal synchrony as a form of maternal responsiveness: Association with language development. - Rohlfing, Katharina; Nomikou, Iris (Language, Interaction and Acquisition)

Tutoring in adult-child-interaction: On the loop of the tutor's action modification and the recipient's gaze - Pitsch, Karola; Vollmer, Anna-Lisa; Rohlfing, Katharina; Fritsch, Jannik; Wrede, Britta (Interaction Studies)
Research of tutoring in parent-infant interaction has shown that tutors - when presenting some action - modify both their verbal and manual performance for the learner (‘motherese’, ‘motionese’). Investigating the sources and effects of the tutors’ action modifications, we suggest an interactional account of ‘motionese’. Using video-data from a semi-experimental study in which parents taught their 8 to 11 month old infants how to nest a set of differently sized cups, we found that the tutors’ action modifications (in particular: high arches) functioned as an orienting device to guide the infant’s visual attention (gaze). Action modification and the recipient’s gaze can be seen to have a reciprocal sequential relationship and to constitute a constant loop of mutual adjustments. Implications are discussed for developmental research and for robotic ‘Social Learning’. We argue that a robot system could use on-line feedback strategies (e.g. gaze) to pro-actively shape a tutor’s action presentation as it emerges.
Keywords: conversation analysis; interactional coordination; adult-child-interaction; feedback; gaze; quantification; social learning; motionese; tutoring

Infants' online perception of give-and-take interactions - Elsner, Claudia; Bakker, Marta; Rohlfing, Katharina; Gredebäck, Gustaf (Journal of Experimental Child Psychology)
This research investigated infants’ online perception of give-me gestures during observation of a social interaction. In the first experiment, goal-directed eye movements of 12-month-olds were recorded as they observed a give-and-take interaction in which an object is passed from one individual to another. Infants’ gaze shifts from the passing hand to the receiving hand were significantly faster when the receiving hand formed a give-me gesture relative to when it was presented as an inverted hand shape. Experiment 2 revealed that infants’ goal-directed gaze shifts were not based on different affordances of the two receiving hands. Two additional control experiments further demonstrated that differences in infants’ online gaze behavior were not mediated by an attentional preference for the give-me gesture. Together, our findings provide evidence that properties of social action goals influence infants’ online gaze during action observation. The current studies demonstrate that infants have expectations about well-formed object transfer actions between social agents. We suggest that 12-month-olds are sensitive to social goals within the context of give-and-take interactions while observing from a third-party perspective.
Keywords: Give-me gesture; Infant; Anticipation; Eye movement; Gesture; Social interaction

Is ostension any more than attention? - Szufnarowska, Joanna; Rohlfing, Katharina; Christine, Fawcett; Gustaf, Gredebäck (Scientific Reports)
According to natural pedagogy theory, infants are sensitive to particular ostensive cues that communicate to them that they are being addressed and that they can expect to learn referential information. We demonstrate that 6-month-old infants follow others' gaze direction in situations that are highly attention-grabbing. This occurs irrespective of whether these situations include communicative intent and ostensive cues (a model looks directly into the child's eyes prior to shifting gaze to an object) or not (a model shivers while looking down prior to shifting gaze to an object). In contrast, in less attention-grabbing contexts in which the model simply looks down prior to shifting gaze to an object, no effect is found. These findings demonstrate that one of the central pillars of natural pedagogy is false. Sensitivity to gaze following in infancy is not restricted to contexts in which ostensive cues are conveyed.
Keywords: Human behavior; Attention

Ich oder Du? Die Therapie der pronominalen Umkehr bei Autismus-Spektrum-Störung - Eine vergleichende Einzelfallstudie nach der Angewandten Verhaltensanalyse mit Verbal Behavior und der Model/Rival-Methode - Krause, Franziska; Richter, Kerstin; Rohlfing, Katharina (Logos)

Studying the Co-Construction of Interaction Protocols in Collaborative Tasks with Humans - Vollmer, Anna-Lisa; Grizou, Jonathan; Lopes, Manuel; Rohlfing, Katharina; Oudeyer, Pierre-Yves (2014 Joint IEEE International Conference on Development and Learning and on Epigenetic Robotics)
Keywords: interaction; communication; co-construction; interaction protocols

A multimodal corpus for the evaluation of computational models for (grounded) language acquisition - Gaspers, Judith; Panzner, Maximilian; Lemme, Andre; Cimiano, Philipp; Rohlfing, Katharina; Wrede, Sebastian (EACL Workshop on Cognitive Aspects of Computational Language Learning)

Developing mutual attention in infancy: Switching gaze roles within multimodal interactions - Nomikou, Iris; Rohlfing, Katharina; Szufnarowska, Joanna

The Development of Purposeful Intersubjectivity - Nomikou, Iris; Rohlfing, Katharina; Leonardi, Giuseppe; Rączaszek-Leonardi, Joanna

Hochschule und Qualität. - Seifert, Andreas (Quality Audit: „Lernen durch Praxisvergleich und Dialog“)

Social Media. A Critical Introduction - Fuchs, Christian

OccupyMedia! The Occupy Movement and Social Media in Crisis Capitalism - Fuchs, Christian

Digital Labour and Karl Marx - Fuchs, Christian

Marx Geri Döndü. Medya, Meta ve Sermaye Birikimi (Turkish translation of 11 contributions in book format)

Special Issue: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work - Definitions, Dimensions and Forms - Fuchs, Christian; Sandoval, Marisol; Prodnik, Jernej A.; Sevignani, Sebastian; Allmer, Thomas (tripleC: Communication, Capitalism & Critique)

Social Media, Politics and the State: Protests, Revolutions, Riots, Crime and Policing in the Age of Facebook, Twitter and YouTube

Critique, Social Media and the Information Society

WikiLeaks and the Critique of the Political Economy - Fuchs, Christian (International Journal of Communication)

Dallas Smythe Today – The Audience Commodity, the Digital Labour Debate, Marxist Political Economy and Critical Theory. Prolegomena to a Digital Labour Theory of Value - Fuchs, Christian (Critical Studies in Communication and Society)

Web 2.0, Prosumption, and Surveillance - Fuchs, Christian; Cao, Jin; Mosco, Vincent; Regan Shade, Leslie (Critical Studies in Communication and Society)

信息资本主义及互联网的劳工 [J] - Fuchs, Christian (新闻大学 (Journalism Bimonthly) 2014 (5))

Theorising Social Media, Politics and the State: An Introduction - Fuchs, Christian; Trottier, Daniel (Social Media, Politics and the State: Protests, Revolutions, Riots, Crime and Policing in the Age of Facebook, Twitter and YouTube)

Anonymous: Hacktivism and Contemporary Politics - Fuchs, Christian (Social Media, Politics and the State: Protests, Revolutions, Riots, Crime and Policing in the Age of Facebook, Twitter and YouTube)

Dallas Smythe Reloaded. Critical Media and Communication Studies Today - Fuchs, Christian (The Audience Commodity in a Digital Age. Revisiting a Critical Theory of Commercial Media)

Introduction: Critique, Social Media and the Information Society in the Age of Capitalist Crisis - Fuchs, Christian; Sandoval, Marisol (Critique, Social Media and the Information Society)

Critique of the Political Economy of Informational Capitalism and Social Media - Fuchs, Christian (Critique, Social Media and the Information Society)

Culture, cC/mmunication & Ideology = Forms of Work - Fuchs, Christian (Media and left)

Social Media as Surveillance: Rethinking Visibility in a Converging World - Allmer, Thomas (European Journal of Communication)

Introduction: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work—Definitions, Dimensions, and Forms - Sandoval, Marisol; Fuchs, Christian; Prodnik, Jernej A.; Sevignani, Sebastian; Allmer, Thomas (Special Issue of tripleC: Communication, Capitalism & Critique)

Why privacy is not enough privacy in the context of “ubiquitous computing” and “big data” - Matzner, Tobias (Journal of Information, Communication and Ethics in Society)
Purpose – Ubiquitous computing and “big data” have been widely recognized as requiring new concepts of privacy and new mechanisms to protect it. While improved concepts of privacy have been suggested, the paper aims to argue that people acting in full conformity to those privacy norms still can infringe the privacy of others in the context of ubiquitous computing and “big data”. Design/methodology/approach – New threats to privacy are described. Helen Nissenbaum's concept of “privacy as contextual integrity” is reviewed concerning its capability to grasp these problems. The argument is based on the assumption that the technologies work, persons are fully informed and capable of deciding according to advanced privacy considerations. Findings – Big data and ubiquitous computing enable privacy threats for persons whose data are only indirectly involved and even for persons about whom no data have been collected and processed. Those new problems are intrinsic to the functionality of these new technologies and need to be addressed on a social and political level. Furthermore, a concept of data minimization in terms of the quality of the data is proposed. Originality/value – The use of personal data as a threat to the privacy of others is established. This new perspective is used to reassess and recontextualize Helen Nissenbaum's concept of privacy. Data minimization in terms of quality of data is proposed as a new concept.

Von der Öko-Bewegung zur nachhaltigen Entwicklung. Überlegungen zum Verhältnis von kritischem Konsum und Konsumkritik - Hälterlein, Jens (Vielfalt und Zusammenhalt. Verhandlungen des 36. Kongresses der Deutschen Gesellschaft für Soziologie in Bochum und Dortmund 2012)

Privacy Issues in Public Discourse. The Case of 'Smart' CCTV in Germany - Hälterlein, Jens (Privacy and Security in the Digital Age)

Digital Workers of the World Unite! A Framework for Critically Theorising and Analysing Digital Labour. In Special Issue: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work - Definitions, Dimensions and Forms, eds. Marisol Sandoval, Christian Fuchs, Jernej A. Prodnik, Sebastian Sevignani and Thomas Allmer - Fuchs, Christian; Sandoval, Marisol (tripleC: Communication, Capitalism & Critique)

Introduction: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work — Definitions, Dimensions, and Forms - Fuchs, Christian; Sandoval, Marisol; Prodnik, Jernej A.; Sevignani, Sebastian; Allmer, Thomas (tripleC: Communication, Capitalism & Critique)

Karl Marx y el estudio de los medios y la cultura hoy (Spanish translation by Roy Alfaro Vargas) - Fuchs, Christian (TELOS. Revista de Estudios Interdisciplinarios en Ciencias Sociales)

Karl Marx and the Study of Media and Culture Today - Fuchs, Christian (Culture Unbound)

WikiLeaks and the Critique of the Political Economy - Fuchs, Christian (WikiLeaks. From Popular Culture to Political Economy)

Digital Prosumption Labour on Social Media in the Context of the Capitalist Regime of Time - Fuchs, Christian (Time & Society)

Wikipedia. An Info-Communist Manifesto - Fuchs, Christian; Firer-Blaess, Sylvain (Television & New Media)

Social Networking Sites in the Surveillance Society: Critical Perspectives and Empirical Findings - Allmer, Thomas; Fuchs, Christian; Kreilinger, Verena; Sevignani, Sebastian (Media, Surveillance and Identity. Social Perspectives)

The Dialectic: Not Just the Absolute Recoil, but the World’s Living Fire that Extinguishes and Kindles Itself. Reflections on Slavoj Žižek’s Version of Dialectical Philosophy in “Absolute Recoil. Towards a New Foundation of Dialectical Materialism“ - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Thomas Piketty’s Book “Capital in the Twenty-First Century”, Karl Marx and the Political Economy of the Internet - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Revisiting the Political Economy of Communication - Fuchs, Christian; Garnham, Nicholas (tripleC: Communication, Capitalism & Critique)

Medios sociales y esfera pública [in Spanish; Social media and the public sphere] - Fuchs, Christian (Telos – Revista de Pensamiento sobre Comunicación, Tecnología y Sociedad)

Social Media and the Public Sphere [Inaugural Lecture] - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Occupy and prefiguration. A roundtable discussion - Fuchs, Christian; Wilding, Adrian; Smith, R.C.; Gunn, Richard; Ott, Michael (Heathwood Press Online)

QTube – Citizen-generated videos for Questions to the Prime Minister. Submission to the House of Commons’-Speaker’s Commission on Digital Democracy. May 19, 2014 - Fuchs, Christian

Review of Manuel Castells’ book “Networks of outrage and hope: Social movements in the Internet age“ - Fuchs, Christian (Media, Culture & Society)

(Dis)Like Facebook? Dialectical and Critical Perspectives on Social Media - Allmer, Thomas (Javnost – The Public: Journal of the European Institute for Communication and Culture)

Philosophers of the World Unite! Theorizing Digital Labour and Virtual Work: Definitions, Forms and Transformations

Selbstdatenschutz - Karaboga, Murat; Masur, Philipp; Matzner, Tobias; Mothes, Cornelia; Nebel, Maxi; Ochs, Carsten; Schütz, Philip; Simo Fhom, Hervais (Whitepaper des Forums Privatheit und Selbstbestimmung in der digitalen Welt)

Sicherheitsethik – Plädoyer für eine neue Bereichsethik - Matzner, Tobias; Nagenborg, Michael; Koch, Heiner (Bereichsethiken im interdisziplinären Dialog)

Der rosafarbene Elefant im Raum. Überlegungen zur fehlenden Wut über die NSA-Affäre - Shnayien, Marie-Luise (onlinejournal kultur & geschlecht)

Der rosafarbene Elefant im Raum. Überlegungen zur fehlenden Wut über die NSA-Affäre - Shnayien, Mary (onlinejournal kultur & geschlecht)
Die Politiken bebilderter Berichterstattung und die Temporalität unserer gegenwärtigen Aufmerksamkeitsökonomie betrachtend, wird den Fragen nachgegangen, wieso die Reaktionen auf die NSA-Affäre so oft von Zynismus oder Resignation gekennzeichnet sind oder sogar ganz ausbleiben, und wer eigentlich betroffen ist und reagieren sollte. Die Überlegungen sind der Versuch, die NSA-Affäre im Spannungsfeld von Technikverliebtheit und Blackboxing, den Bedingungen von Medienereignissen und Geheimdienstpraktiken, der Krise des Journalismus sowie unseren Gewohnheiten im Umgang mit der uns umgebenden rechnenden Umwelt zu situieren.

Subjektivierung als Artikulation diskursiver Ordnungen. Zur Aneignung von Subjektpositionen im Kontext der Entwicklung automatisierter Videoüberwachung - Hälterlein, Jens; Möllers , Norma; Spies, Tina (Zeitschrift für Diskursforschung)

Gier - Zur Kapitalismuskritik in "Johann Holtrop" von Rainald Goetz und in "Gesellschaft mit beschränkter Haftung" von Nora Bossong - Müller, Inez (Leitkulturen und Wertediskussionen)

Bild- und Medientheorien der Naturwissenschaften: Epistemologische Effektivität von Visualisierungen in der Astronomie - Adelmann, Ralf (Visualität, Kultur und Gesellschaft)

Televisuelle Zirkulation sozialer Unsicherheit. Sedimente von white trash in US-amerikanischen Serien - Adelmann, Ralf (Klassenproduktion. Fernsehen als Agentur des Sozialen)

Freundschaften in Facebook. Medialitäten und Politiken - Adelmann, Ralf (Social Network – Die Revolution der Kommunikation)

Listen und Ranken. Zur medialen Strukturierung des Internets - Adelmann, Ralf (Logiken strukturbildender Prozesse: Automatismen)

Computer als Bildmedium - Adelmann, Ralf (Handbuch Medienwissenschaft)

Geld und seine Äquivalente im Film - Adelmann, Ralf (Medienreflexion im Film. Ein Handbuch)

Kettenbriefbeitrag zur Frage "Ihre Medientheorie auf einer Seite?" - Adelmann, Ralf (Zeitschrift für Medienwissenschaft)

ICILS 2013 – Eine international vergleichende Schulleistungsstudie der IEA - Bos, Wilfried; Eickelmann, Birgit; Gerick, Julia; Goldhammer, Frank; Schwippert, Knut; Schaumburg, Heike; Senkbeil, Martin (ICILS 2013 – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern in der 8. Jahrgangsstufe im internationalen Vergleich)

Medienbildung entlang der Bildungskette. Ein Rahmenkonzept für eine subjektorientierte Förderung von Medienkompetenz im Bildungsverlauf von Kindern und Jugendlichen - Eickelmann, Birgit; Aufenanger, Stefan; Herzig, Bardo

Informationskompetenz in formalen und informellen Kontexten – Entwicklung eines pädagogischen Handlungskonzeptes am Beispiel von Wikipedia - Balceris, M.; Aßmann, S.; Herzig, Bardo (Freie Bildungsmedien und Digitale Archive: Medien – Wissen – Bildung)

Gestaltungs- und entwicklungsorientierte Bildungsforschung - Tulodziecki, G.; Herzig, Bardo; Grafe, S. (Enzyklopädie Erziehungswissenschaft Online (EEO), Fachgebiet Medienpädagogik,)

Medienpädagogische Forschung als gestaltungsorientierte Bildungsforschung vor dem Hintergrund praxis- und theorierelevanter Forschungsansätze in der Erziehungswissenschaft - Tulodziecki, G.; Herzig, Bardo; Grafe, S. (MedienPädagogik, Zeitschrift für Theorie und Praxis der Medienbildung.)

Medienbildung entlang der Bildungskette. Ein Rahmenkonzept für eine subjektorientierte Förderung von Medienkompetenz im Bildungsverlauf von Kindern und Jugendlichen - Eickelmann, Birgit; Aufenanger, S.; Herzig, Bardo

Smartphones & Co. in der Schule - Lehren und Lernen mit mobilen Endgeräten - Herzig, Bardo; Martin, A. (Schulmagazin 5-10 3)

Wie wirksam sind digitale Medien im Unterricht? - Herzig, Bardo

Praxis- und theorieorientierte Entwicklung und Evaluation von Konzepten für medienpädagogisches Handeln als gestaltungsorientierte Bildungsforschung - Tulodziecki, G.; Grafe, S.; Herzig, Bardo (Methodologie und Methoden medienpädagogischer Forschung. Jahrbuch Medienpädagogik 10.)

Schule, Identität und Medien. Vom Umgang mit Ambivalenzen - Herzig, Bardo; Aßmann, S. (Jugend, Schule und Identität. Selbstwerdung und Identitätskonstruktion im Kontext Schule)

Grundbildung Medien im Profilstudium im Lehramt - Herzig, Bardo; Aßmann, S.; Klar, T.-M. (Grundbildung Medien in pädagogischen Studiengängen. Reihe: medienpädagogik interdisziplinär)

Entgrenzung von Schule in der digitalen Welt - Herzig, Bardo; Aßmann, S. (School’s out? Informelle und formelle Medienbildung)

How to Define Media in a Mediatized Society? A Media Pedagogical Proposal Inspired by Theoretical Ideas of Castells, Luhmann and Peirce - Herzig, Bardo; Aßmann, S. (MedienPädagogik 24 (18. Juli))

Das Projekt ‚Balu und Du‘ – Kompetenzerwerb bei Mentoren und Mentees - Freitag, Christine; Burgdorf, C. (Kompetenz-Bildung. Soziale, emotionale und kommunikative Kompetenzen von Kindern und Jugendlichen)

Methoden des Vergleichs. Komparatistische Methodologie und Forschungsmethodik in interdisziplinärer Perspektive

Das Vergleichen vergleichen: Erträge der Interdisziplinarität - Freitag, Christine (Methoden des Vergleichs. Komparatistische Methodologie und Forschungsmethodik in interdisziplinärer Perspektive)

Anerkennung und Zugehörigkeit. Was bedeutet es, wenn beim Thema Kirche über die Frage von Zugehörigkeit gesprochen wird? Wer fühlt sich wann und warum einer Gemeinschaft zugehörig? Ein Zwischenruf aus erziehungswissenschaftlicher Perspektive - Freitag, Christine (Katechetische Blätter 5/2014)

Erfahrungen mit dem Peer Learning im Mentorenprogramm „Balu und Du“ - Freitag, Christine; Rumpold, V.; Georgi, K. (Peer Learning durch Mentoring, Coaching & Co)

Einleitung - Freitag, Christine (Methoden des Vergleichs. Komparatistische Methodologie und Forschungsmethodik in interdisziplinärer Perspektive)

Untersuchungen zum ǧihād-Begriff. Theologische und gesellschaftspolitische Einordnungen - Tatari, Muna; Esack, Farid (Gewalt in den Heiligen Schriften vom Islam und Christentum)

Stellvertreter Gottes: Würde und Aufgabe des Menschen - Tatari, Muna; Renz, Andreas (Handbuch christlich–islamischer Dialog. Grundlagen – Themen – Praxis – Akteure)

Handeln Gottes - Antwort des Menschen

Die Einstellung der Koranexegeten im 19. Jahrhundert zur Verfälschung des Christentums - Al-Alusi als Beispiel - Abdelrahem, Mohammed (Das koranische Motiv der Schriftfälschung durch Juden und Christen, Islamische Deutungen und christliche Reaktionen)

Der Islamische Religionsunterricht in NRW - Kamcili-Yildiz, Naciye (Kompetenzorientierung im Religionsunterricht: Von der Didaktik zur Praxis)

Einführung in das islamische Finanzwesen und islamische Wirtschaftsethik - Nassery, Idris (Wirtschaftsethik interreligiös)

(for the ActiFE study group) Multisite pain, pain frequency and pain severity are associated with depression in older adults: results from the ActiFE Ulm study - Denkinger, M.; Lukas, A.; Nikolaus, Th.; Peter, R.; Franke, Sebastian (Age and Ageing)

Berufsfeld Schulbegleitung. Eine Studie zum Einsatz von Schulbegleiter/innen an Förderschulen in NRW - Mays, D.; Franke, Sebastian; Ladinig, B.; Kißgen, R. (Schulverwaltung NRW)

Schulbegleitung an Förderschulen in Nordrhein-Westfalen: Ausgangslage, Studienkonzeption und erste Ergebnisse - Kißgen, R.; Franke, Sebastian; Ladinig, B.; Mays, D.; Carlitscheck, J. (autismus)